JELAJAH RUANG DAN WAKTU MANUSIA PENGHUNI GUA KIDANG - Indah Asikin Nurani (Pubawidya: Jurnal Penelitian dan Pengembangan Arkeologi, 2016)
Gua Kidang is one of the prehistoric dwelling caves with many potential remains of human activities; among others are food processing, bone making and clam shell tool, fireplace and burial ground. The pattern their life showed that they gathered the food sources and raw materials for daily equipment needs. This article describes a reconstruction  the pattern of life in Gua Kidang’s dweller during their occupancy, both through the space and time. The spatial archaeological approach was implemented through a study of Geoarchaeology and paleoanthropology to analyze the data that were collected during the survey and excavation. This article describes the occupancy both on a micro scale (one cave dwelling) and macro scale (Blora kaerst area). In addition, the findings of human skeleton has contributed to the system of burialground during prehistoric dwelling cave.